2005
DOI: 10.1159/000086958
|View full text |Cite
|
Sign up to set email alerts
|

HER2/neu Oncoprotein Overexpression in Epithelial Ovarian Cancer: Evaluation of its Prevalence and Prognostic Significance

Abstract: Introduction: The HER2/neu proto-oncogene encodes a transmembrane receptor protein involved in the development and progression of the majority of cancers. Prior studies have shown that HER2/neu oncogene is overexpressed in approximately 15–30% of ovarian carcinomas. However findings regarding the overexpression and prognosis are still conflicting. Methods: Our retrospective study was performed on 194 ovarian carcinoma tissues obtained at the time of first surgery. The staining procedure for HER2/neu overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 49 publications
1
92
2
1
Order By: Relevance
“…The prognostic role of HER2 overexpression in EOC remains unclear. Some studies proposed that an elevated HER2 level was associated with poorer survival (Lassus et al, 2004;Steffensen et al, 2007), whereas other studies could not demonstrate any association (Verri et al, 2005;Tuefferd et al, 2007). In the meta-analysis conducted by Zhao et al (2013), the prognostic effect of HER2 overexpression was also explored; after reviewing eight studies, they demonstrated that HER2 overexpression was significantly associated with poorer overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic role of HER2 overexpression in EOC remains unclear. Some studies proposed that an elevated HER2 level was associated with poorer survival (Lassus et al, 2004;Steffensen et al, 2007), whereas other studies could not demonstrate any association (Verri et al, 2005;Tuefferd et al, 2007). In the meta-analysis conducted by Zhao et al (2013), the prognostic effect of HER2 overexpression was also explored; after reviewing eight studies, they demonstrated that HER2 overexpression was significantly associated with poorer overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous studies on the expression and clinical significance of HER1 (4-6) and HER2 (3,(7)(8)(9), the role of these receptors are still controversial in ovarian cancer. Furthermore, only few studies have described the tissue expression of the HER3 and HER4 receptor protein in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Her2 is found in 22% of breast cancers, 28% of pulmonary adenocarcinoma, 17% of colorectal adenocarcinomas, 11% of pulmonary squamous, and 11% of gastric adenocarcinomas (37). Her2 overexpression is also found in ovarian and aggressive forms of uterine cancer (38)(39)(40). Recent evidence has implicated Her2 signaling in resistance to the EGFR-targeted cancer drug cetuximab (41).…”
mentioning
confidence: 99%